A study of the relationship among organizational justice, psychological empowerment and organizational citizenship behavior - (:unkn) unknown (Taylor and Francis - Balkema, 2014)
Research in organizational citizenship behaviors (OCBs), perceived organizational justice and psychological empowerment got importance in business management and organizational behavior literature by management researchers and academicians. OCBs have been a research area of interest by considering its relationship with numerous employee perceptions, attitudes and behaviors such as job satisfaction, organizational commitment, trust, leadership and turnover intentions. However, there is a scarce literature on the influences of employees' justice perceptions and psychological empowerment on their OCBs particularly in manufacturing industry setting. Due to this particular view, the current research study was conducted to investigate the influence of organizational justice and psychological empowerment on OCBs of the manufacturing employees. The responses from statistical sample of 217 employees of 20 manufacturing companies in Turkey were analyzed by Structural Equation Modeling (SEM) methodology. The results reveal that organizational justice has a significant positive influence on both psychological empowerment and OCBs; and psychological empowerment has a significant positive influence on OCBs of manufacturing employees. Further, Implications for organizational behavior and management literature, academic researchers and future researchers are presented. © 2014 Taylor & Francis Group.
Keywords: Organizational citizenship behaviors (OCBs); Organizational justice; Psychological empowerment; Structural equation modeling (SEM)